STUDY OF SOIL PHYSICAL QUALITY ON COAL MINE RECLAMATION LAND IN PT. SUMBER BARA ABADI, KUTAI KARTANEGARA DISTRICT - Zulkarnain, Zulkarnain; Hartanto, R M Nur; Rahmi, Abdul (Universitas 17 Agustus 1945 Samarinda, 2025)
Conducting a study on the physical quality of soil on coal mine reclamation land is important for the purpose of carrying out the monitoring and evaluation function of the reclamation activity. The aim of reclamation is to restore, maintain, and improve the quality of soil impacted by mining activities. It is important to evaluate soil physical properties because improving them requires a sufficient amount of time. The results of evaluating soil physical characteristics are recorded as a soil physical quality index that can be used as input for further soil management actions.This research was conducted in PT. Sumber Bara Abadi, Kutai Kartanegara District and the soil analysis was carried out at the Faculty of Agriculture, Mulawarman University from August to November 2022. Surveys and soil sampling were conducted after direct observations and considering the reclamation map of PT. Sumber Bara Abadi. Sampling was done randomly by considering the reclamation year, pioneer plant vegetation, and land slope. The samples were then analyzed in the Soil Laboratory at the Faculty of Agriculture, Mulawarman University. The data analysis used the comparative method and Minimum Data Set relative weights.The analysis results show that the physical soil characteristics of the coal mine reclamation land at the research location are explained in each selected physical characteristic indicator: 1) soil texture varies between clay, clay loam, and sandy clay loam; 2) soil porosity has a poor and good status with the highest value at 54.65% (2020L1) and the lowest at 2018L1 (49.01%); 3) aggregate stability has a very stable and less stable status with the highest value at 291.25% (2018L1) and the lowest value at PitHL2 (43.90%); 4) soil permeability has a slightly slow and moderate status with a value of 1.50 cm.jam-1 (2020L1) and the smallest value at 2018L1 (0.15 cm.jam-1); 5) bulk density has a moderate and slightly poor status with soil density ranging from a value of 1.34 g.cm-3 (2018L1) to the lowest bulk density value at PitHL4 (1.09 g.cm-3); 6) surface rocks have a high status (15.5046.00%); 7) solum depth at the research location has a moderate to shallow status with a depth of 68.00 cm (PitHL1) and the lowest depth value at PitHL2 (31.67 cm). The physical quality of soil at the research location is expressed in the physical soil quality index (IKFT) with a moderate and slightly high category with a value of (2.705-3.588), followed by limiting factors of the physical soil quality index (IKFT), including surface rocks found in high numbers at each research location, high bulk density, low solum depth, and low aggregate stability.